Telepsychiatry and other technologies for integrated care: evidence base, best practice models and competencies. (2nd November 2018) - Hilty, Donald M.; Sunderji, Nadiya; Suo, Shannon; Chan, Steven; McCarron, Robert M.
Abstract: Telehealth facilitates integrated, patient-centred care. Synchronous video, telepsychiatry (TP), or telebehavioural health provide outcomes as good as in-person care. It also improves access to care, leverages expertise at a distance, and is effective for education and consultation to primary care. Other technologies on an e-behavioural health spectrum are also useful, like telephone, e-mail, text, and e-consults. This paper briefly organizes these technologies into low, mid and high intensity telehealth models and reviews the evidence base for interventions to primary care, and, specifically, for TP and integrated care (IC). Technology, mobile health, and IC competencies facilitate quality care. TP is a high intensity model and it is the best-studied option. Studies of IC are preliminary, but those with collaborative and consultative care show effectiveness. Low- and mid-intensity technology options like telephone, e-mail, text, and e-consults, may provide better access for patients and more timely provider communication and education. They are also probably more cost-effective and versatile for health system workflow. Research is needed upon all technology models related to IC for adult and paediatric primary care populations. Effective healthcare delivery matches the patients' needs with the model, emphasizes clinician competencies, standardizes interventions, and evaluates outcomes.